Employment and Skills Strategies in Southeast Asia Setting the Scene - Martinez-Fernandez, Cristina (OECD Local Economic and Employment Development (LEED) Papers, 2010)
The Southeast Asian region has experienced some of the highest growth rates in the world, with investments in skills playing a significant role in helping national economies to adjust to changes in working practices, advances in technology, and challenges associated with globalisation. In some countries this process has been more successfully managed and significant advances have been achieved in growth rates and employment levels, but in others it has resulted in stagnation of economic sectors, underemployment, rising unemployment levels and social exclusion for large sections of society